Non fungible Token (NFT): Sharia And Accounting Perspectives - Rindika, Santika Maya (Jurnal Ilmiah Ekonomi Islam, 2024)
Non-Fungible Tokens (NFTs) are digital assets within blockchain networks that present potential as alternative digital investments. Their use extends beyond conventional e-commerce, influencing financial reporting practices. However, NFT transactions involving cryptocurrency are controversial as the Indonesian Ulema Council (MUI) has prohibited their use. This study, through a review of literature and practical experience in NFT e-commerce, examines NFT transactions from both Islamic jurisprudence and financial accounting perspectives. Within the Islamic framework, NFTs can be considered intellectual property rights, compliant with Islamic principles. However, transactions involving cryptocurrency may be invalid due to prohibitions. From an accounting standpoint, NFTs are classified as intangible assets with their value based on procurement and utilization methods. Additionally, NFT creators or sellers follow revenue recognition principles. This dual perspective provides insights into the complex interplay between Islamic legality and financial accounting in NFT transactions. The study concludes that NFTs, as digital assets, are generally halal. However, Muslim entities should carefully assess whether their transactions involve cryptocurrencies. Given the growing popularity and diversity of digital assets, including NFTs, further research into their accounting treatment in practical scenarios is recommended to expand on these conceptual findings.